DIGITALISASI INFORMASI TERHADAP PENYIARAN RADIO ARDAN BANDUNG - Nabila, Vira Putri; Virsa, Fathur Rorsyid; Puteri, Sanny Syaffanash Vianty (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Dharmawangsa, 2024)
Broadcasting media, namely radio and television, is a form of mass media that is efficient in reaching a very large audience. Therefore broadcast media plays a very important role in communication science in general and mass communication science in particular. The publishing industry in Indonesia shows its rapid development. One of the radio stations is Ardan Radio. This research uses a qualitative approach using the case study method. This research was carried out through an interview process, in this research an interview process was carried out with Muhamad Faisal as producer of Ardan Radio & Broadcaster in 2021 in the Ardan School school bus program. Ardan Radio Bandung has a broadcast format that prioritizes pop music, both local and international. Apart from that, they also present news, updates, and interesting segments such as talk shows, games, and interactions with listeners via telephone or social media. This radio has succeeded in building a strong image among young people and the people of Bandung. Ardan Radio has the tagline